2007
DOI: 10.2533/chimia.2007.716
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocifens and Ferrocifenols as New Potential Weapons against Breast Cancer

Abstract: Depending on the presence or absence of the estrogen receptor in the cells, breast cancer today is often treated by endocrine therapy (tamoxifen) or chemotherapy, respectively. We present now a new paradigm for breast cancer treatment, taking advantage of concepts in bioorganometallic chemistry. In this way, we have synthesized molecules containing an organometallic moiety (ferrocene), and a biovector (hydroxytamoxifen), yielding compounds which display a new therapeutic spectrum consisting of antiestrogenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
152
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 166 publications
(155 citation statements)
references
References 33 publications
3
152
0
Order By: Relevance
“…This heavy element offers a capacity for good stabilization of certain high degrees of oxidation (+VI) and for an excellent metal-to-ligand back-donation at low oxidation states (+II, +III) leading to more stable complexes than those of Fe or Ru in biological media. The potential of this so far neglected metal in biomedically-oriented organometallic complexes deserves to be better studied especially when comparisons with neighboring series of Fe and Ru are easy to obtain [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This heavy element offers a capacity for good stabilization of certain high degrees of oxidation (+VI) and for an excellent metal-to-ligand back-donation at low oxidation states (+II, +III) leading to more stable complexes than those of Fe or Ru in biological media. The potential of this so far neglected metal in biomedically-oriented organometallic complexes deserves to be better studied especially when comparisons with neighboring series of Fe and Ru are easy to obtain [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] We have shown that some ferrocene derivatives are very active against cancer cells. The addition of a ferrocenyl moiety to selected polyaromatic phenols, [13][14][15][16] amines, 17,18 amides, 19 and esters 19,20 can potentiate their antiproliferative effects against breast and prostate cancer cells. For example, 4-hydroxytamoxifen, the active metabolite of the breast cancer drug tamoxifen, 21 shows limited cytotoxicity against hormone-refractory breast cancer cells (LC 50 for MDA-MB-231 cells:…”
Section: Introductionmentioning
confidence: 99%
“…[9] We have found that the most effective compounds (IC 50 values less than 1 μM) possess, like 2 and 3, a ferrocene-ene-para-phenol entity. [10,11] The ferrocene appears to act as a stimulus for a mild intramolecular oxidation involving the phenol group, leading to the facile production of quinone methides, the formation, structure, and electrophilic behavior of which we have established. [12][13][14][15] A structure-activity relationship (SAR) study extended to include a number of ferrocene complexes has allowed us to identify another molecule, the cyclic diphenol 4 derived from [3]ferrocenophane, with toxicity on MDA-MB-231 cells that is noticeably greater than that of Fc-diOH (3; IC 50 values of 0.09 μM for 4 vs. 0.6 μM for 3).…”
Section: Introductionmentioning
confidence: 97%